A randomized controlled trial of patient recall after detailed written consent versus standard verbal consent in adults with routine orthopaedic trauma. (2023) - Aslam, A. M.; Kennedy, J.; Seghol, H.; Khisty, N.; Nicols, T. A.; Adie, S.
No abstract available